Significant Increase in Depression in Women With Primary Dysmenorrhea: A Systematic Review and Cumulative Analysis - Zhao, Shankun; Wu, Weizhou; Kang, Ran; Wang, Xiaolan (Frontiers in Psychiatry, 2021)
Women with primary dysmenorrhea are vulnerable to develop a depressive disorder, a common form of psycho-disturbance. However, clinical findings are inconsistent across studies and the evidence has not been previously synthesized. This study aims to investigate whether primary dysmenorrhea is associated with a higher risk of depression via a cumulative analysis. Four electronic databases were systematically searched for the eligible studies. The combined effect was assessed by analyzing the relative risk (RR) and standard mean diﬀerences (SMD) with a 95% confidence interval (CI). This cumulative analysis was registered on the PROSPERO (ID: CRD42020169601). Of 972 publications, a total of 10 studies involving 4,691 participants were included. Pooled results from 6 included studies showed that primary dysmenorrhea was associated with a significant depressive disorder (RR=1.72, 95%CI: 1.44 to 2.0, P < 0.001; heterogeneity: I2 = 0 %, P = 0.544). In addition, synthesis results from 2 studies provided the BDI scores suggested that dysmenorrhea had significantly higher scores when compared to non-dysmenorrhea (SMD = 0.47, 95%CI: 0.31 to 0.62, P < 0.001; heterogeneity: I2 = 0 %, P = 0.518). However, in the 2 studies providing the PROMIS T-Score, the pooled result showed that there was no significant difference between women with dysmenorrhea and those without dysmenorrhea (P =0.466). The overall quality of the evidence in our study was judged to MODERATE. The present study has confirmed the positive relationship between primary dysmenorrhea and depression. Social supports and medical help from the pain management physicians or psychologists are the important interventions for women with dysmenorrhea suffering depressive disorder.